Surgical Management of Preputial Prolapse in Crossbred Bulls: A Report of Five Cases - Kumar, Ankush; Rohilla, Shivani (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Due to pendulous and longer sheaths and excessive  preputial skin, certain breeds especially those of the  Bos indicus or Bos indicus cross bulls are prone to prolapse  of the prepuce, thus rendering it susceptible to injury or  irritation. Prolapse of the prepuce is characterized by the  inner lining of its sheath protruding and everting outward,  without showing any inclination to retract (Arthur et al., 1996). Small preputial abrasions lead to formation of  swelling and edema which in turn exaggerate further  preputial prolapse and hence create a vicious cycle,  which may worsen the condition and lead to prolapse of  additional lengths of prepuce, its trauma or mutilation  combined with desiccation of the exposed tissues leading  to necrosis (Maxwell and Edmondson, 2009). Preputial  prolapses are classified in four categories as per the  severity of edema and injury (Prado and Morgan, 2002).  The present paper reports category III to IV preputial  prolapse which were successfully managed with surgical  intervention in five crossbred bulls.
Keywords: Surgical Management; Small preputial